2022
DOI: 10.1002/cssc.202201405
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Devising Computational Strategies for Dual‐Ion Batteries

Abstract: Dual-ion batteries (DIBs) have been considered a viable alternative to increasingly costly and hazard-prone lithium-ion batteries (LIBs), which have reached a level of saturation. DIBs differ from LIBs in the way that the cations and anions originate from the electrolyte, thus signifying the active role played by electrolyte. In this Review, the major developments in research in the field of DIBs are summarized with a major emphasis on computational approaches in this direction. The various computational metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 114 publications
(269 reference statements)
0
13
0
Order By: Relevance
“…Tapping into renewable energy sources requires the development of efficient energy storage devices such as batteries and capacitors . In recent years, dual-ion batteries (DIBs) based on aluminum and graphite electrodes are emerging as attractive alternatives to high-cost lithium-ion batteries (LIBs). Such DIBs exhibit attractive features such as high voltage, low cost, and high volumetric capacity. However, the limited electrochemical window (ECW) potential of commonly used organic electrolytes causes intense side reactions and reduced working voltage for all batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…Tapping into renewable energy sources requires the development of efficient energy storage devices such as batteries and capacitors . In recent years, dual-ion batteries (DIBs) based on aluminum and graphite electrodes are emerging as attractive alternatives to high-cost lithium-ion batteries (LIBs). Such DIBs exhibit attractive features such as high voltage, low cost, and high volumetric capacity. However, the limited electrochemical window (ECW) potential of commonly used organic electrolytes causes intense side reactions and reduced working voltage for all batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…With ever-increasing energy demands, the need for efficient and large-scale energy storage devices has also increased to connect the producer with the consumer by offering easy portability and the freedom to use according to requirement. , Among, energy storage devices, Li-ion batteries composed of electrodes with Li intercalation/adsorption capability are being traditionally utilized in the current scenario. , However, along with prolonged usage, various safety issues have emerged, which coupled with the raw material and infrastructure costs, mandate the search for alternative battery mechanisms . Dual-ion batteries, especially LiPF 6 , AlCl 3 based batteries have become an attractive research area featuring various advantages over Li-ion batteries . The dual-ion batteries majorly use metal anodes such as Li, Si, Al, and Sn for an easier electroplating/stripping process. , Among them, Al electrodes feature high gravimetric (2980 mAh g –1 ) and volumetric (8040 mAh cm –3 ) capacity, thereby making it a suitable electrode material which is also abundant and safer to handle. , …”
Section: Introductionmentioning
confidence: 99%
“…5 Dualion batteries, especially LiPF 6 , AlCl 3 based batteries have become an attractive research area featuring various advantages over Li-ion batteries. 6 The dual-ion batteries majorly use metal anodes such as Li, Si, Al, and Sn for an easier electroplating/ stripping process. 7,8 Among them, Al electrodes feature high gravimetric (2980 mAh g −1 ) and volumetric (8040 mAh cm −3 ) capacity, thereby making it a suitable electrode material which is also abundant and safer to handle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to understand to what extent each factor affects the anion intercalation potential of GLG, density functional theory (DFT) was employed. Various studies have reported on the intercalation potentials of various anions, including PF 6 – anion, into graphite using DFT. It has been proved that it is possible to reproduce experimentally obtained reaction potentials with considerable quantitative accuracy by using appropriate calculation conditions. In this study, the influence of the interlayer expansion energy and the electronic states of GLG on the anion intercalation potential was investigated using DFT calculations.…”
Section: Introductionmentioning
confidence: 99%